Life cycle-based enviroeconomic and thermal analyses of the inlet air-cooled microturbine systems with liquefied natural gas cold energy - Kanbur, Baris Burak (2020)
Liquefied natural gas cold utilization systems are used in the processes of three different inlet air-cooled microturbine systems to investigate the overall performances with respect to the life cycle-related enviroeconomic and thermal approaches as new defined aspects. The inlet air cooling applications increase the thermal efficiency and the power generation rate roundly by 3.2 and 7.7%, respectively, while the payback period of the inlet-air cooled system is closely higher than the conventional case. The life cycle-based environmental payback periods of the inlet air-cooled systems are found 3.25, 7.77, and 6.16% less than the conventional systems since the inlet air cooling applications achieve 3.25, 2.54, and 2.47% emission reductions of 30, 65, and 200 kW microturbine models, respectively. The integration of the life cycle assessment parameters increases the classical enviroeconomic parameters roundly by 100%. Moreover, different electricity and gas prices are studied to have more reliable data about the real engineering applications of the proposed systems. India, USA and Mexico are selected as the LNG importer countries for the case studies, and it is seen that the cold energy based inlet air cooling applications are more commercially viable for the regions where the fuel costs are relatively high whereas the systems become unfeasible with the low electricity prices.